A PILLAR OF FAITH AND CULTURE: TRACING THE LEGACY OF THE MESJID TABLIGHIYAH GAREGEH - Rambe, Replin Anwar; Muslim, Kori Lilie (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2025)
This research was motivated by the existence of the Tablighiyah Mosque in Garegeh Village, a historic building that has significant value in the development of Islam in the area. The mosque was founded in 1963 and plays a central role in the social, religious, and cultural dynamics of the Garegeh community. The purpose of this study is to uncover the history of the establishment of the Tablighiyah Mosque and the role of national figures in its inauguration, namely Muhammad Hatta as the nation's proclaimer, H. Abdul Malik Karim Amrullah (Buya Hamka) as a Minangkabau cleric, and Drs. H. Muhammad Jusuf Kalla, the 10th Vice President of the Republic of Indonesia. The method used is qualitative research with a descriptive-narrative approach. Data was obtained through document studies in the form of archival photos, interviews, and literature studies. The research process followed the steps of the historical method, namely heuristics, verification, interpretation, and historiography. The results of the research show that the Tablighiyah Mosque is not only historically valuable, but also serves as a center for religious, social, cultural arts, educational, and economic activities for the Garegeh community.